The problems of translating аrabic poetry (Journal of Oriental Studies, 2016)
The article examines ways of promoting translations of Arabic poetry into Kazakh, exploring issues related to the transfer - a kindof creative thinking development of nations today and in the future.
Keywords: the Arabic poetr; translation of poetic works; artistic translation